Clinical manifestations and pregnancy outcomes of COVID-19 in indonesian referral hospital in central pandemic area - Muhammad Ilham Aldika Akbar; Khanisyah Erza Gumilar; Rino Andriya; Manggala Pasca Wardhana; Pungky Mulawardhana; Jimmy Yanuar Anas; Ernawati; Muhammad Ardian Cahya Laksana; Gustaaf Dekker (Korean Society of Obstetrics and Gynecology, 2022)
Objectives Data on the clinical manifestations and pregnancy outcomes of pregnant women with COVID-19 are limited, particularly in developing countries. The aim of this study was to analyze the clinical manifestations and pregnancy outcomes in COVID-19 maternal cases in a large referral hospital in Indonesia. Methods This study used a prospective cohort design and included all pregnant women with suspected COVID-19. Subjects were divided into COVID-19 and non-COVID-19 groups based on the results of real-time polymerase chain reaction (RT-PCR) for severe acute respiratory syndrome coronavirus 2. Clinical characteristics, laboratory results, and pregnancy outcomes were compared between the two groups. Results Of the 141 suspected maternal cases, 62 cases were COVID-19-confirmed (43.9%), while 79 suspected cases were negative (56.1%). The clinical manifestations and laboratory findings between the two groups were not significantly different (P>0.05). However, the maternal mortality directly caused by COVID-19 was significantly higher than that in the non-COVID-19 group (8.3% vs. 1.3%; P=0.044; odd ratio, 6.91; 95% confidence interval, 0.79-60.81). Conclusion The clinical manifestations and laboratory results of suspected pregnant women with positive and negative RT-PCR COVID-19 results were similar. However, within the Indonesian setting, COVID-19 significantly increases the risk of maternal death through both direct and indirect factors.